Lippincott visual nursing a guide to diseases, skills, and treatments - Kantor, Debra (Wolters Kluwer, 2019)
For an image-rich guide to the clinical concepts and on-the-unit skills needed to treat the major common diseases, look no further than the fully updated Lippincott Visual Nursing, 3rd Edition. Using clear, concise definitions backed by abundant images, this vital text explains disease pathophysiology, with expert guidance on anatomy, symptoms, assessment skills, and hands-on patient care. Ideal for students, new nurses, and experienced nurses needing a review, this is a must-have guide to providing appropriate, effective patient care. -- Provided by publisher.